A mixed helium–oxygen shell in some core-collapse supernova progenitors. Issue 1 (28th April 2018) - Gofman, Roni Anna; Gilkis, Avishai; Soker, Noam
Abstract: We evolve models of rotating massive stars up to the stage of iron core collapse using the mesa code and find a shell with a mixed composition of primarily helium and oxygen in some cases. In the parameter space of initial masses of 13–40 M⊙ and initial rotation velocities of 0–450 km s −1 that we investigate, we find a mixed helium–oxygen (He-O) shell with a significant total He-O mass and with a helium to oxygen mass ratio in the range of 0.5–2 only for a small fraction of the models. While the shell formation due to mixing is instigated by rotation, the pre-collapse rotation rate is not very high. The fraction of models with a shell of He-O composition required for an energetic collapse-induced thermonuclear explosion is small, as is the fraction of models with high specific angular momentum, which can aid the thermonuclear explosion by retarding the collapse. Our results suggest that the collapse-induced thermonuclear explosion mechanism that was revisited recently can account for at most a small fraction of core-collapse supernovae. The presence of such a mixed He-O shell still might have some implications for core-collapse supernovae, such as some nucleosynthesis processes when jets are present, or might result in peculiar sub-luminous core-collapse supernovae.